Different impairment of immune and inflammation functions in short and long-term after ischemic stroke - Li, Wen-Xing (Am J Transl Res, 2017)
Ischemic stroke therapy and prognosis outcomes largely depend on the time periods after symptom onset. This study aims to explore the difference of global gene expression profiles and impairment of biological functions between short-term and long-term after stroke onset. We compared three short-term (3 h, 5 h and 24 h) and a long-term (6-month) gene expression levels by a multi-platform microarray data integration method. RankProd was used to calculate the differentially expressed genes between stroke patients and controls. DAVID Bioinformatics Resources was utilized to determine affected biological functions. Consensus cluster and hierarchical cluster methods were employed to compare the gene expression patterns of the commonly biological functions among these four time course groups. The results showed that severe impairment of inflammation and immune related functions in 5 h and 24 h after symptom onset. However, these functions were less affected in the 3 h and the 6-month groups. In addition, several key genes (CCL20, THBS1, EREG, and IL6 et al.) were dramatically down-regulated in 5 h and 24 h groups, whereas these genes showed no change or even a slight contrary expression in 3 h or 6-month groups. This study has identified the large differences of altered immune and inflammation functions based on gene levels between short and long-term after stroke onset. The findings provide valuable insight into the clinical practice and prognosis evaluation of ischemic stroke.